Engineering 2D Multifunctional Ultrathin Bismuthene for Multiple Photonic Nanomedicine - Wang, Yuemei; Feng, Wei; Chang, Meiqi; Yang, Jiacai; Guo, Yuedong; Ding, Li; Yu, Luodan; Huang, Hui; Chen, Yu; Shi, Jianlin (Advanced functional materials, 2021)
2D monoelemental nanomaterials (Xenes) have shown tremendous potential for versatile biomedical applications. Bismuth, as a heavy element in pnictogens, has acquired massive research interest due to its unique optical performance, high biocompatibility, stability, and relatively low cost. However, the utilization of 2D bismuthene in nanomedicine has not been achieved because of the difficulty in engineering bismuthene with crucial structural/compositional characteristics for satisfying strict biomedical requirements. Herein, to address this Gordian knot, a facile strategy to intercalate and delaminate Bi bulk for generating mass few‐layered 2D bismuthene with high yield by employing a water molecule mediated freezing–thawing process and sodium borohydride‐triggered reduction treatment is proposed. The resulting 2D bismuthene displays good optical performance in the near‐infrared (NIR) biowindow and can be excited via red light for reactive oxygen species generation, enabling applications in multiple photonic cancer nanomedicine settings, including photothermal hyperthermia and photodynamic therapy. Utilizing the intrinsic desirable optical absorbance and strong X‐ray attenuation of bismuthene, dual photonic therapy can be conducted under the supervision of photoacoustic/computed tomography guided multimodal imaging. This research not only offers a potential mass‐production ready, cost‐effective, and eco‐efficient methodology for engineering 2D Xenes, but also exploits an innovative 2D bismuthene based photonic cancer nanomedicine. To capture the potential biomedical application of 2D bismuthene, herein, a facile methodology to intercalate and delaminate Bi bulk for generating mass few‐layered 2D multifunctional ultrathin bismuthene is proposed, which enables applications in multiple photonic oncological nanomedicine settings, including photothermal hyperthermia and photodynamic therapy.